Enhanced Electromagnetic Wave Absorption Properties of Poly(3,4-ethylenedioxythiophene) Nanofiber-Decorated Graphene Sheets by Non-covalent Interactions - Zhang, Xiang; Huang, Ying; Liu, Panbo (Nano-Micro Letters, 2015)
Graphene sheets (GNs) have high conductivity, but they exhibit weak electromagnetic (EM) wave absorption performance. Here, poly (3,4-ethylenedioxythiophene) (PEDOT) nanofibers were decorated on the surface of GNs in which the residual defects and groups act as the active sites and therefore are beneficial for the deposition of PEDOT nanofibers. The SEM images display that PEDOT nanofibers are successfully decorated on the surface of GNs through in situ polymerization. The diameter of the PEDOT nanofibers were ranged from 15 to 50 nm with hundreds of nanometers in length. The EM wave absorption properties of graphene, PEDOT, and GNs-PEDOT were also investigated. Compared to pure graphene and PEDOT, the EM wave absorption properties of GNs-PEDOT improved significantly. The maximum value of R L was up to −48.1 dB at 10.5 GHz with a thickness of only 2 mm. Meanwhile, the absorption bandwidth of R L values below −10 dB was 9.4 GHz (5.8–12.3, 12.9–15.8 GHz) in the thickness of 1.5–3 mm. The enhancement is attributed to the modification of PEDOT and the unique structure of nanofibers. On one hand, the deposition of PEDOT nanofibers on the surface of GNs decreases the conductivity of graphene, and makes impedance match better. On the other hand, the unique structure of PEDOT nanofibers results in relatively large specific surfaces areas, providing more active sites for reflection and scattering of EM waves. Therefore, our findings demonstrate that the deposition of conducting polymers on GNs by non-covalent bond is an efficient way to fabricate strong EM wave absorbers.